An Analysis of Student Satisfaction and its Relationship with Academic and Social Factors in University Dropout - Maria Esteban; Ana B. Bernardo; Elena Blanco; Palmira Oserin (International Journal of Educational Psychology)
Over the last 50 years, Higher Education has experienced significant development, which has been associated with challenges that have yet to be solved. In this sense, university dropout is a global phenomenon that worries universities all over the world. Many research studies describe the possible causes of this phenomenon, but the most interesting are those that, due to their predictive potential, have the possibility of preventing it. The aim of this article is to study how important students perceive the different reasons for dropout in relation to the idea of abandoning the degree. For this purpose, the Spanish version of the Questionnaire of Motives for Higher Education Dropout (QMA_es; Almeida et al., 2019) was applied to a sample of 927 first- and second-year university students. These data have been processed using educational data mining (EDM) techniques, obtaining a decision tree that correctly classifies the sample in 81.1%. The results show that variables related to student satisfaction (satisfaction with academic choice, satisfaction with performance, and satisfaction with the financial situation) and to the academic and social environments play a predominant role in the approach to dropout, above other institutional, financial, and wellbeing variables.